RAINFALL VARIABILITY AND ITS ASSOCIATION TO THE TRENDS OF CROP PRODUCTION IN MVOMERO DISTRICT, TANZANIA - Msafiri Mkonda (European Scientific Journal, ESJ, 2014)
A study was carried in two villages of Mvomero and Makuyu of Mvomero District, Tanzania. The overall objective of this study was to assess the relationship between the trend of rainfall variability and that of crop production in the study area. Both secondary and primary were used. Primary data were obtained using different Participatory Research Approaches (PRA) including, focus group discussions and household questionnaires. A sample size of 7% of the total households was sampled for the study. Findings showed that there is a relationship between the two variables. In years where rainfall was decreasing, the crop yields decreased too. The study concluded that, the possession of climatic knowledge by the farmers helps them to be aware of the climate change impacts. This help to increase their resilience regarding climate change impacts and improve food security.